The Effect of Environmental Turbulence, Competitive Strategy, Dynamic Capability, and Organizational Learning on Sustainable Competitive Advantage of Business in Creative Industry - Sihite, Mislan; Fatchuroji, Acep; Rijal, Syamsu (International Journal of Business, Law, and Education, 2026)
The paper investigates the roles of environmental turbulence, competitive strategy, dynamic capability, and organizational learning in the creative sector in relation to sustainable competitive advantage. The creative sector operates in a highly dynamic environment, with technological advancements, changing consumer tastes, and other factors, making it difficult for organizations in the sector to maintain long-term competitiveness in the market. A quantitative explanatory model was used in the research to investigate the proposed relationships between the components of the conceptual framework. A sample of the target population was selected using a structural equation model in order to analyze the impact of the components of the model in determining sustainable competitive advantage in the creative sector. The research results show that organizations in the creative sector are positively affected by environmental turbulence with respect to competitive strategy, dynamic capability, and organizational learning. Dynamic capability, competitive strategy, and organizational learning have a significant positive impact on sustainable competitive advantage with dynamic capability having the highest impact. Therefore, organizations in the creative sector can maintain sustainable competitive advantage under turbulence if they are capable of adopting dynamic strategies, possessing dynamic capabilities, and improving.